Heallth Educaltion On The Level Of Knowledge Albout The Halzalrds Of Smoking In Youth - Ramdani, Endan; Marliany, Heni; Apipudin, Aap (LPPM STIKes Muhammadiyah Ciamis, 2024)
The World Heallth Orgalnizaltion (WHO) staltes thalt smoker is not only done by men, but allso by women. Globall daltal staltes thalt 63% of men alnd 4.5% of women alre smokers. Smoking is one of the alddictive substalnces thalt caluse heallth halzalrds thalt alre mostly in demalnd by malny men. Smoking behalvior in aldolescents will generallly increalse alccording to the stalge of development alnd increalse in the frequency alnd intensity of smoking which caluses nicotine dependence. Nicotine caln caluse alddiction not only in alctive smokers but allso in palssive smokers. In Indonesial, novice smokers alre teenalgers, this behalvior begins in aldolescence alnd increalses to become regulalr smokers within al few yealrs. The realson the resealrcher chose SMPN 6 Raljaldesal is becaluse smoking almong teenalgers is al phenomenon thalt often occurs in Raljaldesal District. Objective: to determine the effect of heallth educaltion on the level of knowledge albout the dalngers of smoking in aldolescents. Methods: This resealrch uses qualntitaltive alnallyticall methods with Pre-Experimentall design in the form of One-Group Pri-Test alnd Post-Test. The populaltion in this study were 227 students. Salmpling in this study used non-ralndom salmpling with the type of salmpling quotal als malny als 69 respondents. Results: the results of the study balsed on the Palired salmple t test showed al sig vallue. 2-taliled) = 0.000 < = 0.05. Conclusion: there is al difference or influence between heallth educaltion on the level of knowledge albout the dalngers of smoking in aldolescents alt SMPN 6 Raljaldesal, Raljaldesal District, Cialmis Regency.